Ecology and worldview - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Is there a relationship between spiritual and religious beliefs and how we treat our environment and eco-system? Some scholars have asserted that religion encourages people to focus more on the next life instead of dealing with the problems and injustices of this life. But in this program we'll hear from scholars who believe that most religions and spiritual traditions teach and encourage perspectives and behaviors that could, if practiced, have a positive and healing effect on our environment and our eco-system.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Ecology; Ideology